The dynamic behavior of a parametrically excited time-periodic MEMS taking into account parametric errors - Peruzzi, N. J. [UNESP]; Chavarette, Fábio Roberto [UNESP]; Balthazar, José Manoel [UNESP]; Tusset, Angelo Marcelo; Perticarrari, Amanda Liz Pacifico Manfrim[UNESP]; Brasil, Reyolando Reyolando Manoel Lopes Rebello da Fonseca (SAGE Publications, 2015)
Micro-electromechanical systems (MEMS) are micro scale devices that are able to convert electrical energy into mechanical energy or vice versa. In this paper, the mathematical model of an electronic circuit of a resonant MEMS mass sensor, with time-periodic parametric excitation, was analyzed and controlled by Chebyshev polynomial expansion of the Picard interaction and Lyapunov-Floquet transformation, and by Optimal Linear Feedback Control (OLFC). Both controls consider the union of feedback and feedforward controls. The feedback control obtained by Picard interaction and Lyapunov-Floquet transformation is the first strategy and the optimal control theory the second strategy. Numerical simulations show the efficiency of the two control methods, as well as the sensitivity of each control strategy to parametric errors. Without parametric errors, both control strategies were effective in maintaining the system in the desired orbit. On the other hand, in the presence of parametric errors, the OLFC technique was more robust.
Keywords: Mems; Time-delayed feedback control; Optimal linear feedback control; Nonlinear control; Feedforward control; Parameter uncertainties